Inside lives : psychoanalysis and the growth of the personality - Waddell, Margot, 1946- (Tavistock Clinic series., 2002)
This is the second edition of the remarkable Inside Lives, expanded with a chapter on the last years of the life cycle. It provides a perspective on the relationship between psychoanalytic theory and the nature of human development which has not been available in written form. A volume from the Tavistock Clinic Series, this book traces the interplay between influences - internal and external - which contribute to a person's character strength and sense of identity.